2016
DOI: 10.1016/j.cortex.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived egocentric distance sensitivity and invariance across scene-selective cortex

Abstract: Behavioral studies in many species and studies in robotics have demonstrated two sources of information critical for visually-guided navigation: sense (left-right) information and egocentric distance (proximal-distal) information. A recent fMRI study found sensitivity to sense information in two scene-selective cortical regions, the retrosplenial complex (RSC) and the occipital place area (OPA), consistent with hypotheses that these regions play a role in human navigation. Surprisingly, however, another scene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 58 publications
10
44
0
Order By: Relevance
“…Importantly, the pattern of responses in OPA was not driven by domain-general motion sensitivity or low-level visual information. These findings are consistent with a recent hypothesis that the scene processing system may be composed of two distinct systems: one system supporting navigation (including OPA, RSC, or both), and a second system supporting other aspects of scene processing, such as scene categorization (e.g., recognizing a kitchen versus a beach) (including PPA) (Dilks et al, 2011; Persichetti & Dilks, 2016). This functional division of labor mirrors the well-established division of labor in object processing between the dorsal (“how”) stream, implicated in visually-guided action, and the ventral (“what”) stream, implicated in object recognition (Goodale & Milner, 1992).…”
Section: 4 Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, the pattern of responses in OPA was not driven by domain-general motion sensitivity or low-level visual information. These findings are consistent with a recent hypothesis that the scene processing system may be composed of two distinct systems: one system supporting navigation (including OPA, RSC, or both), and a second system supporting other aspects of scene processing, such as scene categorization (e.g., recognizing a kitchen versus a beach) (including PPA) (Dilks et al, 2011; Persichetti & Dilks, 2016). This functional division of labor mirrors the well-established division of labor in object processing between the dorsal (“how”) stream, implicated in visually-guided action, and the ventral (“what”) stream, implicated in object recognition (Goodale & Milner, 1992).…”
Section: 4 Discussionsupporting
confidence: 91%
“…If a region represents first-person perspective motion through scenes, then it should respond significantly more to the Dynamic Scene condition than the Static Scene condition (p = 0.01, FWE corrected). We found several regions showing this pattern of results: i) the left lateral superior occipital lobe (which overlapped with OPA as defined in a comparable group-level contrast of scenes vs. objects using data from the Localizer scans), consistent with the above ROI analysis; ii) a contiguous swath of cortex in both hemispheres extending from the lateral superior occipital lobe into the parietal lobe, including the intraparietal sulcus and superior parietal lobule, consistent with other studies implicating these regions in navigation (Burgess, 2008; Kravitz, Saleem, Baker, & Mishkin, 2011; Marchette et al, 2014; Persichetti & Dilks, 2016; Spiers & Maguire, 2007; van Assche, Kebets, Vuilleumier, & Assal, 2016); and iii) the right and left precentral gyrus, perhaps reflecting motor imagery related to the task (Malouin, Richards, Jackson, Dumas, & Doyon, 2003). Crucially, none of these regions showed overlapping activation in the contrast of Dynamic Faces vs. Static Faces (p = 0.01, FWE corrected), suggesting that this activation is specific to motion information in scenes.…”
Section: 3 Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It has recently been proposed that, within the scene-selective network, the OPA is particularly well suited for guiding navigation in local space (26), although there is also evidence that it plays a role in scene categorization (27,28). The OPA is sensitive to changes in the chirality (i.e., mirror-image flips) and egocentric depth of visual scenes (26,29), both of which reflect changes in navigationally relevant spatial parameters. A recent study using transcranial magnetic stimulation showed that the OPA has a causal role in perceiving spatial relationships between objects and environmental boundaries, but not between objects and other objects (30).…”
Section: Discussionmentioning
confidence: 99%